KETIKA AI MENJADI MESIN HOAKS: SIAPA YANG BERTANGGUNG JAWAB? - Nathanael Orlando Situmorang; M. Ferdyan Pratama; R. N. M. Abyaz Fayyaza; Adelia Khairunisa Darmadi; Hafiz Abbad Alhaim; Haidar Bintang Bahran (CV. Denasya Smart Publisher, 2026)
The rapid development of generative Artificial Intelligence (AI) technology in Indonesia not only facilitates human activities but also poses serious threats through the massive production and dissemination of hoaxes in digital spaces. This article aims to analyze the mechanisms of generative AI technology (such as deepfakes and disinformation bots) in producing hoaxes, map the legal and ethical responsibilities of relevant actors, evaluate the readiness of national regulations and digital literacy, and formulate systemic solutions. This paper employs a mixed-methods approach, combining secondary content analysis of 5,000 verified hoax posts (quantitative) with a normative juridical method through legislative analysis (qualitative). The findings reveal that platform recommendation algorithms accelerate the spread of hoaxes up to six times faster than authentic news, driven by automated bot activity (61% of viral trends) and a 550% surge in deepfake content. Furthermore, a legal vacuum exists, as the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP) have yet to specifically regulate the accountability of developers, platforms, or users in AI governance. This article recommends the implementation of a hybrid verification system (AI NLP with 92–97% accuracy combined with human fact-checkers), the establishment of adaptive regulations mandating algorithmic transparency, the creation of an independent supervisory body, and the acceleration of national digital literacy programs.